Design a control system for observing vibration and temperature of turbines - Omar Farhan Al-Hardanee; İlyas Çankaya; Abdulmuttalib A. Muhsen; Huseyin Canbolat (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The core of a typical hydroelectric power plant is the turbine. Vibration and overheating in a turbine occur when water flows through it, and with increased vibration and high temperature, it will cause the turbine blade to break. In this study, the control and monitoring system is designed to predict and avoid any error before it occurs. This process is achieved by measuring vibration and temperature using sensors and sending signals through the Arduino to the graphical user interfaces (GUI), the system compares the signals taken from the sensors with the permissible limits, and when the permissible limits are exceeded, the processor takes appropriate measures to open and close the turbine gates, where the data is displayed in matrix laboratory graphical user interfaces (MATLAB’s GUI) screen. In this way, monitoring is done, and the appropriate action are taken to avoid mistakes.